Population structure of KPC carbapenemase-producing Klebsiella pneumoniae in a long-term acute-care rehabilitation facility: identification of a new lineage of clonal group 101, associated with local hyperendemicity. Issue 1 (2nd January 2020) - Arena, Fabio; Di Pilato, Vincenzo; Vannetti, Federica; Fabbri, Laura; Antonelli, Alberto; Coppi, Marco; Pupillo, Roberto; Macchi, Claudio; Rossolini, Gian Maria
Abstract : In this work, we used a whole-genome sequencing (WGS) approach to study the features of KPC-producing Klebsiella pneumoniae (KPC-Kp) spreading in a large Italian long-term acute-care rehabilitation facility (LTACRF), and to track the dynamics of dissemination within this setting. Thirty-eight, non-replicated, KPC-Kp isolates from colonized patients (either already colonized at admission or colonized during admission), collected during 2016, were subjected to antimicrobial-susceptibility testing and WGS. All isolates were resistant to β-lactams, with the exception of ceftazidime/avibactam (97.4 % susceptible). The second most effective agent was fosfomycin, followed by colistin, trimethoprim/sulfamethoxazole, gentamicin and amikacin (92.1, 86.8, 60.5, 44.7 and 50 % of susceptibility, respectively). A large proportion of isolates ( n =18/38, 47.4%) belonged to clonal group (CG) 101, and most of them ( n =15) to a new sequence type (ST) designated as ST2502. All the CG101 isolates had a capsule locus type KL17. The ST2502 harboured the genes encoding for the yersiniabactin siderophore and the ArmA methylase, conferring high-level resistance to aminoglycosides. The second most represented lineage of isolates (16/38, 42.1%) belonged to ST512 of CG258. Analysing WGS data, we were able to ascertain the common origin of some isolates imported from other hospitals, and to track several clusters of in-LTACRF cross-transmissions. The results revealed that, in peculiar epidemiological settings such as LTACRF, new KPC-Kp clones different from those prevailing in acute-care hospitals and associated with uncommon resistance and virulence determinants can successfully emerge and disseminate.